Сижу на уроке туплю 1.p+3\p+4 - p-3\p-4 2.7p+q\p^2-pq + p+7q\q^2-pq

Zeerorrrrrr Zeerorrrrrr    2   08.08.2019 05:30    1

Ответы
GoodSmileEweryDay GoodSmileEweryDay  04.10.2020 04:32
P+3          p-3       (p+3)(p-4) - (p-3)(p+4) 
  -     =       =
p+4            p-4          P^2 - 16

p^2 -4p +3p -12 -p^2-4p+3p+12  )       -2p
=   
             p^2-16                                    p^2 -16

7p+g            p+7g            7p+g        p+7g            7pg+g^2 -p^2-7gp
  +    =    -  =  =
p(p-g)          g(g-p)            p(p-g)        g(p-g)            pg(p-g)

g^2 -p^2        (p-g)(p+g)                  p +g
= -  =    -   
gp(p-g)          gp (p-g)                        pg
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра